Robotic-assisted mediastinal lymphadenectomy in lung cancer: a narrative review - Adamica, Dávid; Tulinský, Lubomír; Kepičová, Markéta; Dzurňáková, Paula; Ihnát, Peter; Mitták, Marcel; Varga, Adam; Neoral, Čestmír; Martínek, Lubomír (Journal of robotic surgery, 2025)
The objective of this study is to undertake a narrative review of the oncological adequacy of mediastinal lymphadenectomy performed via robot-assisted thoracic surgery (RATS) in comparison with video-assisted thoracic surgery (VATS) and thoracotomy for non-small cell lung cancer (NSCLC). The focus of the review is on lymph node yield, nodal station dissection, and nodal upstaging rates. A narrative review of literature published in the last decade was conducted using PubMed, Cochrane, and Web of Science databases. Studies examining mediastinal lymphadenectomy outcomes for RATS, VATS, or thoracotomy were included in the discussion. The analysis of 19 studies from diverse geographical regions showed that in six out of nine comparative studies, RATS demonstrated superior lymph node retrieval compared to VATS, with statistically significant differences. RATS achieved comparable or superior nodal station dissection rates and showed particular advantages in upstaging from clinical N0 to pathological N2 status. Additionally, RATS demonstrated favourable perioperative outcomes with reduced morbidity and mortality rates compared to conventional approaches. RATS represents a reliable and oncologically sound approach to mediastinal lymphadenectomy, with potential advantages over conventional techniques. Its enhanced visualization and precision make it an increasingly utilised option for NSCLC treatment in centres with robotic capabilities.
Keywords: Mediastinum; mediastinum; výsledek terapie; Robotic Surgical Procedures; Thoracic Surgery, Video-Assisted; roboticky asistované výkony; Lymph Node Excision; torakotomie; Treatment Outcome; lymfadenektomie; hrudní chirurgie video-asistovaná; Thoracotomy; lidé; nádory plic; Carcinoma, Non-Small-Cell Lung; Humans; nemalobuněčný karcinom plic; Lung Neoplasms